Global Age-sex-specific Fertility, Mortality, Healthy Life Expectancy (HALE), and Population Estimates in 204 Countries and Territories, 1950–2019: A Comprehensive Demographic Analysis for the Global Burden of Disease Study 2019 - Wang, Haidong; Abbas, Kaja M; Abbasifard, Mitra; Abbasi-Kangevari, Mohsen; Abbastabar, Hedayat; Abd-Allah, Foad; Abdelalim, Ahmed; Abolhassani, Hassan; Abreu, Lucas G; Abrigo, Michael RM; Abushouk, Abdelrahman I; Adabi, Maryam; et al. (Elsevier BV, 2020)
No abstract.